PEMBINAAN KOMPETENSI PEDAGOGIK GURU SD PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Zuliarni Zuliarni (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
Results of the study revealed that mastery of pedagogical competence of teachers is low, characterized by the manufacture of RPP result of the adoption PL and prepared students for the purposes of surveillance, media and methods are still conventional, low-grade teaching is not thematic. Development of pedagogical competence of teachers is not yet optimal. Coaching by the school principal is done through classroom observation, meetings with teachers, and the assignment of teachers to follow KKG. Coaching by a senior teacher of the junior teachers in the form of a discussion or share teaching experience, as well as self-learning teachers. Constraints in coaching comes from internal and external. Effort in overcoming the obstacles in the guidance is advised teachers to continue their education to S1 as well as participate in various training, teacher performance assessment, contact the UNP to provide training to teachers in order to improve teachers' pedagogical competence. This study suggested that the acquisition and development of pedagogical competence of elementary school teachers UNP Development Laboratory can be improved through training and on going coaching to produce learning and quality education.